2018
DOI: 10.1007/s10815-018-1239-9
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNAs involved in cellular proliferation have altered expression profiles in granulosa of young women with diminished ovarian reserve

Abstract: The miRNA pattern identified critical functions in cell proliferation and survival associated with DOR. GC in women with DOR seems to respond differently to the LH surge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 51 publications
0
33
1
Order By: Relevance
“…We also observed a moderate, statistically significant correlation between decreased serum H19 expression and decreased AMH. Altered expression profiles of microRNAs, another class of noncoding RNAs, has been linked with poor ovarian reserve in plasma and serum [24,25], whole ovaries [26], follicular fluid [27], granulosa cells [28][29][30], and oocytes [31], and two studies have reported differential expression of piwi-interacting RNAs in GCs and oocytes from women with DOR [31,32]. However, little is known about the role of long noncoding RNAs such as H19 in ovarian aging.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a moderate, statistically significant correlation between decreased serum H19 expression and decreased AMH. Altered expression profiles of microRNAs, another class of noncoding RNAs, has been linked with poor ovarian reserve in plasma and serum [24,25], whole ovaries [26], follicular fluid [27], granulosa cells [28][29][30], and oocytes [31], and two studies have reported differential expression of piwi-interacting RNAs in GCs and oocytes from women with DOR [31,32]. However, little is known about the role of long noncoding RNAs such as H19 in ovarian aging.…”
Section: Discussionmentioning
confidence: 99%
“…E-MTAB-391′s platform was the A-MEXP-1564-IIIumina HumanRef-8 WG-DASL v3 Expression BeadChip. We directly extracted the data from the DOR miRNAs used in a previous study ( Woo et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Considering this coadjutant relationship between oocyte and GC, exploring the alteration of GCs from women with DOR may provide a deeper understanding for DOR pathogenesis. Previous studies have investigated the mRNA expression profiles of ovarian CCs ( Greenseid et al, 2011 ) and GCs ( Chin et al, 2002 ; Skiadas et al, 2012 ) in addition to miRNA expression patterns ( Chen et al, 2017 ; Woo et al, 2018 ) in DOR patients. These studies typically had different inclusion criteria for DOR patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this coadjutant relationship between oocyte and GC, exploring the alteration of GCs from women with DOR may provide a deeper understanding for DOR pathogenesis. Previous studies have investigated the mRNA expression profiles of ovarian CCs (Greenseid et al, 2011) and GCs (Chin et al, 2002;Skiadas PeerJ reviewing PDF | (2020:03:46424:2:0:NEW 1 Aug 2020) Manuscript to be reviewed et al, 2012) in addition to miRNA expression patterns (Chen et al, 2017;Woo et al, 2018) in DOR patients. These studies typically had different inclusion criteria for DOR patients.…”
Section: Introductionmentioning
confidence: 99%